Investigating the potential for a user-driven electricity monitoring application to provide useful electricity consumption patterns - Mantel, Jessica Kirsten (Department of Computer Science, 2017)
Conventional electricity usage monitoring involves complex data collection via costly and intrusive hardware installation. There is a perceived need for a simple and affordable tool that provides users with feedback about their electricity consumption without the hardware installation. This study involves the design and development of a user driven mobile and desktop application that provides users with information on electricity usage patterns and historical trends. The application was designed using Ionic Framework, a tool ideal for the design of hybrid applications that are compatible with both desktop Windows devices and mobile Android devices. The goal of the research will be that the user will track their appliance usage on the application whilst taking electricity meter readings at regular intervals to calculate appliance-specific consumption. The data is added to the mobile or desktop application, which then provides users with a comprehensive display of the electricity usage patterns and trends. The objective is to provide users with the information required so that they can start understanding their electricity consumption better and it is a first step towards empowering the user to make smart decisions at home that will reduce their electricity consumption. The USE (Usefulness, Satisfaction, Ease of Use and Ease of Learning) questionnaire was used to gather user experience feedback from participants about user experience. The USE questionnaire tests the perceived Usefulness, Satisfaction, Ease of Use and Ease of Learnability The 31 individuals who initially volunteered to take part in the study are all residents of the City of Cape Town Municipality, aged between 20 and 80 years old. Not all participants are home owners; some are tenants in their premises. The sample group was selected on a convenience basis, and social media group posts were also used to reach individuals with a potential interest in the study. The two motivating factors that were considered to identify individuals who could potentially have an interest in the study were cost saving and environmental impact. 21 volunteers completed the study and returned the USE questionnaire. The study findings showed that all participants believe that using the application helped them to better understand their electricity consumption.